Rethinking trade union density: A new index for measuring union strength - Anne Metten (Industrial Relations Journal, 2021)
Although trade union density is the most influential and most commonly used indicator to map trade union strength, comparing between countries and time, the author argues that trade union density is lacking both specificity and comparability. Additionally, many studies on industrial relations neglect developing countries. Therefore, the paper offers a new concept based on a combination of different theoretical approaches that identify determinants of trade union strength involving developing countries. On that basis, the author creates a novel, composite index that is better at capturing trade union strength than previous indices. First evaluations of this collective labour force index, which covers the years 2000 to 2016 in 72 countries, show that it is quite capable of doing so.
Keywords: 330